AGAMA DAN POLITIK: TEOLOGI PEMBEBASAN SEBAGAI ARENA PROFETISASI AGAMA - Wasisto Raharjo Jati (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2014)
This article aims to analyze the comparative study of the liberation theology perspective. The notion of liberation theology is a form of transformative theology that is concerned with issues of equality and social justice. The relationship amidst religion and politics is reciprocal due to there are conflicts of interest between both entities. The emergence of liberation theology itself arises because of the politicization of religion has become more acute and chronic so it needs to be transformed. The thought of liberation theology is basically grown in the famous case of Latin America with the spirit church of the poor. However, within Islam, it also found a similar essence that Islam also teaches that there egalitarianism, equality, and social justice. The article will elaborate on this comparison of liberation theology.